Materi dan Prosedur Penetapan Gugatan Perwakilan Kelompok, Studi Perbandingan: Indonesia dan Amerika Serikat - Laras Susanti (Fakultas Hukum Universitas Gadjah Mada, 2018)
Abstract. Background of this article is, although it was first emerged in Common Law system countries, the practice of class action has been growing in Indonesia. This mechanism brings an opportunity to simplified the court’ process and to reduce the risk of disparity judgements. This article found similarities and differences scope and procedure of certification in Indonesia and the USA. Before examining the case, a presiding judges, accordingly to Supreme Court Regulation Number 1 Year 2002 concerning Procedure of Class Action, have to determine whether the case is eligible to be examine as class action case. This procedure is universally well-known as certification mainly focuses on the fulfilment of class action’s substantive requirements: numerosity, commonality, typicality and adequacy of representation and formal requirements. The similar requirements are also implemented in the USA accordingly to Federal Rule of Civil Procedure, Rule 23 Class Action. However, in those countries have different procedure when it comes to legal remedy to the certification order, mechanism to opt-out in case of settlement or withdrawal, the role of judge in assisting poor litigants and determining counsel’s fee. This article recommends Indonesia has to amend the Supreme Court regulation to add provisions on legal remedy, and mechanism to opt-out in case of settlement or withdrawal.